Penerapan Total Quality Management terhadap produk cacat pada PT. Sinar Pure Foods International di Bitung - Dasmasela, Vicy M.; Morasa, Jenny; Rondonuwu, Sintje (Universitas Sam Ratulangi, 2020)
Total quality management is a philosophy that requires changes in behavior at all levels of the organization with attention on the importance of consumer satisfaction. Or in other words, the improvement of which is carried out continuously by every person in the organization to understand, meet and even exceed customer expectation. This study aims to determine how the implementation of total quality management to defects product in the PT. Sinar Pure Foods International in Bitung. Type of research used in this thesis research is descriptive research type. The type of data used in this research is qualitative data. The results of the study found that quality is an important factor in a company especially in the production. Total quality management has been applied effectively on PT. Sinar Pure Foods International in Bitung.